Plasmablastic Lymphoma with Coexistence of Chronic Lymphocytic Leukemia in an Immunocompetent Patient: A Case Report and Mini-Review - Hatzimichael, Eleftheria; Papathanasiou, Konstantina; Zerdes, Ioannis; Flindris, Stefanos; Papoudou-Bai, Alexandra; Kapsali, Eleni (Case Reports in Hematology, 2017)
Background. Plasmablastic lymphoma (PBL) is a rare, aggressive B-cell lymphoma with poor prognosis usually found in the oral cavity of HIV-positive patients. Chronic lymphocytic leukemia (CLL) is an indolent B-cell lymphoma with a variable clinical course. Transformation of CLL to PBL as Richter’s syndrome is rare while coexistence of CLL and PBL at diagnosis is even rarer. Case Report. We describe a case of a male immunocompetent patient with an ileum-cecum valve mass and a soft tissue mass at the left humerus with histologic evidence of PBL with coexistence of CLL in the bone marrow and peripheral blood. Amputation of the patient’s left arm was inevitable, and the patient was started on bortezomib and dexamethasone. However, prolonged hospitalization was complicated by aspiration pneumonia, and the patient passed away. Conclusions. No standard of care exists for patients with PBL, and prognosis remains dismal. Concomitant presentation of hematological malignancies becomes increasingly recognized, and further insight is needed in order to delineate whether they originate from the same clone or from different ones.